DEPRESSIVE DISORDERS IN EPILEPSY - Koralia Todorova; Mariana Arnaoudova (Peytchinski Publishing, 2010)
Depressive disorders are the most frequent psychiatric comorbidity in epilepsy but very often remain unrecognized and untreated. We examined 103 epileptic patients, aged 18-60 years, 40 males and 63 females, for the presence of interictal depressive disorder. All subjects underwent clinical psychiatric examination, including evaluation on Hamilton Depression Rating Scale (HAM-D-17). A questionnaire for demographic and seizure-related variables was also completed. Concurrent depressive disorder (clinically presented according to ICD-10 diagnostic criteria) affected 28.3% of all evaluated patients. Based on HAM-D-17 scores depression was defined as mild - 80% of all depressed patients, moderate - 17% and severe - 3%. Atypical presentation of interictal depressive disorder was frequent. Depression has a tremendous effect on one's family, social and psychological functioning, even more than the actual seizure frequency and severity. Diagnostic difficulties come through the atypical mode of presentation of depressive disorders in epilepsy. Proper neuropsychiatric evaluation is essential for improving treatment and quality of life for patients with epilepsy.